Low-Dose or High-Dose Rocuronium Reversed with Neostigmine or Sugammadex for Cesarean Delivery Anesthesia: A Randomized Controlled Noninferiority Trial of Time to Tracheal Intubation and Extubation - Štourač, Petr; Adamus, Milan; Seidlová, Dagmar; Pavlík, Tomáš; Janků, Petr; Křikava, Ivo; Mrozek, Zdeněk; Procházka, Martin; Klučka, Jozef; Štoudek, Roman; Bartikova, Ivana; Kosinová, Martina; et al. (Anesthesia and analgesia, 2016)
BACKGROUND: Rocuronium for cesarean delivery under general anesthesia is an alternative to succinylcholine for rapid-sequence induction of anesthesia because of the availability of sugammadex for reversal of neuromuscular blockade. However, there are no large well-controlled studies in women undergoing general anesthesia for cesarean delivery. The aim of this noninferiority trial was to determine whether rocuronium and sugammadex confer benefit in time to tracheal intubation (primary outcome) and other neuromuscular blockade outcomes compared with succinylcholine, rocuronium, and neostigmine in women undergoing general anesthesia for cesarean delivery. METHODS: We aimed to enroll all women undergoing general anesthesia for cesarean delivery in the 2 participating university hospitals (Brno, Olomouc, Czech Republic) in this single-blinded, randomized, controlled study. Women were randomly assigned to the ROC group (muscle relaxation induced with rocuronium 1 mg/kg and reversed with sugammadex 2-4 mg/kg) or the SUX group (succinylcholine 1 mg/kg for induction, rocuronium 0.3 mg/kg for maintenance, and neostigmine 0.03 mg/kg for reversal of the neuromuscular blockade). The interval from the end of propofol administration to tracheal intubation was the primary end point with a noninferiority margin of 20 seconds. We recorded intubating conditions (modified Viby-Mogensen score), neonatal outcome (Apgar score <7; umbilical artery pH), anesthesia complications, and subjective patient complaints 24 hours after surgery. RESULTS: We enrolled 240 parturients. The mean time to tracheal intubation was 2.9 seconds longer in the ROC group (95% confidence interval, -5.3 to 11.2 seconds), noninferior compared with the SUX group. Absence of laryngoscopy resistance was greater in the ROC than in the SUX groups (ROC, 87.5%; SUX, 74.2%; P = 0.019), but there were no differences in vocal cord position (P = 0.45) or intubation response (P = 0.31) between groups. No statistically significant differences in incidence of anesthesia complications or in neonatal outcome were found (10-minute Apgar score <7, P = 0.07; umbilical artery pH, P = 0.43). The incidence of postpartum myalgia was greater in the SUX group (ROC 0%; SUX 6.7%; P = 0.007). The incidence of subjective complaints was lower in the ROC group (ROC, 21.4%; SUX, 37.5%; P = 0.007). CONCLUSIONS: We conclude that rocuronium for rapid-sequence induction is noninferior for time to tracheal intubation and is accompanied by more frequent absence of laryngoscopy resistance and lower incidence of myalgia in comparison with succinylcholine for cesarean delivery under general anesthesia.
Keywords: těhotenství; gamma-Cyclodextrins; Neuromuscular Blockade; lidé; mladiství; pooperační bolest; cholinesterasové inhibitory; výsledek terapie; Adult; Middle Aged; Single-Blind Method; Anesthesia, Obstetrical; Female; laryngoskopie; celková anestezie; Adolescent; Humans; Cesarean Section; myalgie; antidota; sukcinylcholin; Antidotes; Česká republika; nedepolarizující myorelaxancia; nervosvalová blokáda; Anesthesia, General; lidé středního věku; Neostigmine; Succinylcholine; androstanoly; Myalgia; mladý dospělý; císařský řez; Androstanols; Neuromuscular Nondepolarizing Agents; Laryngoscopy; gama-cyklodextriny; ženské pohlaví; neostigmin; Pregnancy; Intubation, Intratracheal; Time Factors; Young Adult; Czech Republic; jednoduchá slepá metoda; Pain, Postoperative; Treatment Outcome; časové faktory; porodnická anestezie; Cholinesterase Inhibitors; dospělí; intratracheální intubace